Food for thought! Inulin-type fructans: Does the food matrix matter?. (March 2022) - Jackson, Peter Philip James; Wijeyesekera, Anisha; Theis, Stephan; van Harsselaar, Jessica; Rastall, Robert Adrian
Graphical abstract: Highlights: Inulin has been used in a wide array of food-based supplementation studies. The bifidogenic effect of inulin appears to be independent of the food matrix. Different study designs make it challenging to draw more comprehensive conclusions. Further studies are needed to confirm if food matrices alter microbial selectivity. Abstract: Food matrices can be described as the final composition of a food product which results from complex interactions between compounds found within different ingredients and the processing parameters used in production. These factors, not only impact on the final structure of a product, but also have the potential to alter both the structural integrity and bioavailability of potentially beneficial compounds present, for example, dietary fibres. As a result, there is growing curiosity amongst the scientific community on whether the food matrix may impact on the prebiotic efficacy of inulin-type fructans. Therefore, the purpose of this review is to explore previous food-based inulin-type fructan supplementation studies to determine whether the food matrix directly impacts on their prebiotic efficacy. Our working hypothesis is that other potentially prebiotic ingredients and components present within the food may alter inulin-type fructans prebiotic effect.